PRE-TREATMENT AND ENZYMATIC HYDROLYSIS OF BANANA (Musa acuminata x balbisiana) PSEUDOSTEM FOR ETHANOL PRODUCTION - Galileo E. Araguirang; Arianne Joyce R. Arizala; Eden Beth B. Asilo; Jamie Louise S. Batalon; Erin B. Bello; James Paul T. Madigal; Jerice R. Monge; Nicole Angelique L. Sanchez; Francisco B Elegado (Agro Bali : Agricultural Journal, 2020)
Banana (M. acuminata x balbisiana) is an abundant lignocellulosic waste material in large plantations all over the Philippines, especially in Mindanao, which can be utilized as substrate in producing high-value products like ethanol. To compensate for the low yield based on total weight of substrate due to the high moisture content of banana pseudostem, there is the primary challenge to make the conversion of this lignocellulosic biomass into monomeric sugar and then into ethanol more efficiently in order to achieve yields that would make it cost-competitive. Hence, this study evaluated the effects of solid loading, incubation time and amount of enzyme on yield of reducing sugars in the enzymatic hydrolysis process and attempted to optimize the significant factors by Response Surface Methodology (RSM), specifically using Box-Behnken design. There was significant improvement on the reducing sugar yield of the pretreated banana pseudostem at 20 h incubation time, 15 g solid loading and 0.55 % enzyme concentration. Ethanol production was observed to be higher in the detoxified substrate although biomass was higher for the non-detoxified substrate. As to our knowledge, the present study is the first attempt to produce second generation ethanol using banana pseudostem waste as feedstock in the Philippines.